2016
DOI: 10.1002/ece3.2357
|View full text |Cite
|
Sign up to set email alerts
|

Airport noise predicts song timing of European birds

Abstract: Anthropogenic noise is of increasing concern to biologists and medical scientists. Its detrimental effects on human health have been well studied, with the high noise levels from air traffic being of particular concern. However, less is known about the effects of airport noise pollution on signal masking in wild animals. Here, we report a relationship between aircraft noise and two major features of the singing behavior of birds. We found that five of ten songbird species began singing significantly earlier in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 40 publications
2
68
1
1
Order By: Relevance
“…Regarding birdsong, studies have shown a general pattern of song modifications that appear in response to noise, such as upshifted frequency (Slabbekoorn and Peet, 2003;Nemeth and Brumm, 2009;Verzijden et al, 2010;Bermúdez-Cuamatzin et al, 2012), increased song amplitude (Cynx et al, 1998;Brumm, 2004;Brumm et al, 2009), modifications in temporal parameters of song (Slabbekoorn and den Boer-Visser, 2006;Díaz et al, 2011;Ríos-Chelén et al, 2013) or changes in the timing of the dawn chorus (Fuller et al, 2007;Arroyo Solís et al, 2013;Dominoni et al, 2016). In many bird species, it has been found that populations living near anthropogenic noise sources sing at higher frequencies, partly avoiding masking (Slabbekoorn and Peet, 2003;Nemeth and Brumm, 2009;Verzijden et al, 2010;Ríos-Chelén et al, 2012;Roca et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding birdsong, studies have shown a general pattern of song modifications that appear in response to noise, such as upshifted frequency (Slabbekoorn and Peet, 2003;Nemeth and Brumm, 2009;Verzijden et al, 2010;Bermúdez-Cuamatzin et al, 2012), increased song amplitude (Cynx et al, 1998;Brumm, 2004;Brumm et al, 2009), modifications in temporal parameters of song (Slabbekoorn and den Boer-Visser, 2006;Díaz et al, 2011;Ríos-Chelén et al, 2013) or changes in the timing of the dawn chorus (Fuller et al, 2007;Arroyo Solís et al, 2013;Dominoni et al, 2016). In many bird species, it has been found that populations living near anthropogenic noise sources sing at higher frequencies, partly avoiding masking (Slabbekoorn and Peet, 2003;Nemeth and Brumm, 2009;Verzijden et al, 2010;Ríos-Chelén et al, 2012;Roca et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence suggesting that birds advance the onset of dawn chorus when living in noisy conditions (Fuller et al, 2007;Gil et al, 2014;Dominoni et al, 2016;Dorado-Correa et al, 2016). The question remains open as to whether this shift of singing activity is a byproduct of noise-induced perturbations on the birds' behavior, as suggested by some authors (Arroyo Solís et al, 2013), or an adaptive modification to counter act the effect of noise later on the day (Fuller et al, 2007;Dominoni et al, 2016). Taking an optimization approach and assuming that singing earlier has negative effects due to energy balance and predation (McNamara et al, 1987), it would be expected that birds should advance dawn chorus in order to avoid noisy conditions if this leads to improved signal transmission.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations